Influence of selected features of forests on forest landscape aesthetic value – example of SE Poland - Dudek, Tomasz (Journal of Environmental Engineering and Landscape Management, 2018)
The study was designed to examine the relationship between features of forests and the quality of forest landscapes, and to determine the strength of effect of the features in the aesthetic value of the landscape. The methodology applied to assess forest landscapes took into account the following features: forest site humidity, age of forest, terrain slope, site index of stands, species composition of the tree layer, under-story cover, colour and composition, mosaic-like, as well as horizontal structure of the tree stands. The study was conducted in temperate forests located in Central-Eastern Europe – more precisely – in south-eastern Poland. In the investigated area the dominating tree species are: Pinus sylvestris L., Abies alba Mill., Fagus sylvatica L. and Quercus L. They cover 42.2%, 20.8%, 20.4% and 6.5% of the total forest area, respectively. The findings show that nearly 1% of the area of the examined forests within the relevant territory are characterized with very high landscape value, over 67% with high, 31% with medium, and less than 0.5% with low landscape value. A strong relationship occurs between terrain slope vs. aesthetic quality of landscape as well as forest site humidity vs. aesthetic quality of landscape. Weak effect was observed for site index of stands vs. aesthetic quality of landscape, and moderate relationship was identified in the case of the remaining features. The findings show the strength of relationship between the features of forests and the aesthetic quality of landscapes, consequently providing a tool for forest managers to develop attractive forest landscapes in selected areas.